Olvídate del cuarto propio: Jorge Luis Borges y Gloria Anzaldúa leen a Virginia Woolf. - González Mateos, Adriana (Estudios de Teoría Literaria, 2022)
This article traces the importance of Virginia Woolf's A Room of One's Own in the works of Jorge Luis Borges and Gloria Anzaldúa. Even when Borges translated the essay, he later made efforts to distance himself from it, attributing it to his mother, Leonor Acevedo. However, it's impact can be read in his essays "Las versiones homéricas" and "El escritor argentino y la tradición", where he defined his aesthetic project. In a similar way, in "Speaking In Tongues: A Letter To 3rd World Women Writers", where she discusses her conflicts and coincidences with white feminists, Gloria Anzaldúa invites to forget Woolf's book, but as this article shows, she finds many coincidences with Woolf's description of the problems faced by women writers. Both for Borges and Anzaldúa, Woolf's essay marked crucial topics and limits for their later work.